Investigation Of Metal-Organic Decomposed (MOD) Cerium Oxide (Ceo2) Gate Deposited On Silicon And Gallium Nitride Substrates Via Spin-On Coating Technique - Quah, Hock Jin (2010)
Metal-organic decomposed (MOD) Ce(h precursor has been spin coated on n-type Si and n-type GaN substrates with thickness in the range of 45-90 nm. Prapenanda Ce02 yang disediakan dengan teknik penguraian organik logam telah diserakkan ke atas wafer Si dan GaN beljenis n dengan ketebalan dalam Iinkungan 45-90 run.